Optimization the Role of APIP (Government Internal Supervisory Apparatus) in the Region as a Preventive Action in the Criminal Act of Corruption in Indonesia - Winarsi, Sri; Abrianto, Bagus Oktafian; Nugraha, Xavier; Danmadiyah, Shevierra (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the position and role of APIP in region on preventing corruption according to statutory regulations and to find out the ideal concept for APIP in the region. This research is a legal research conducted with normative research using the statutory approach and conceptual approach. It is known that various laws and regulations governing APIP’s position in region consistently, which is under the regional head. Regarding the role of APIP in region on preventing corruption, it starts through the existence of a new function in Government Regulation Number 72 of 2019 concerning Amendments to Government Regulation Number 18 of 2016 concerning Regional Apparatuses. Furthermore, the most important thing that becomes the solution is the repositioning of APIP in region. APIP in region cannot be continually placed under the regional head. This will greatly affect their performance. As long as APIP in the region is still under the shadow of the regional head, APIP in the region will not be able to become a supervisor in the region. APIP’s position in the region should be under the Ministry of Internal Affairs, hence APIP in region will be more courageous to take action. Departing from this, APIP in regions will no longer responsible to the regional head. The first thing to do in realizing this is to create a second amendments to Government Regulation Number 18 of 2016 concerning Regional Apparatuses. Departing from this reposition, technical matters regarding position and rank adjustments will be able to follow. In addition, clear requirements must be established regarding qualifications to be APIP inspectors in the regions. Then, a fit and proper test should be made and involving the community and independent institutions. It is certainly intended that the inspector has full of responsibility to the community.